The experience and influence of fear after anterior cruciate ligament reconstruction: an interview study with young athletes - Kvist, J.; Bengtsson, J.; Lundqvist, C. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background Despite good physical function, many athletes do not return to sports after an anterior cruciate ligament reconstruction (ACLR). One important reason for this is fear of new injury. The aim of this study was to investigate young athletes` experiences of knee-related fear after an ACLR and how they perceive this fear to affect them in their sporting and everyday life.